Peran Guru Pendidikan Agama Kristen dalam Membentuk Emotional Quotient anak Generasi Alpha Menyonsong Indonesia Emas 2045 - Vriandi Sitohang; Cristian Seldjatem (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the role of Christian Religious Education Teachers in shaping the Emotional Quotient (EQ) of Alpha Generation children, as one of the efforts to welcome the Golden Indonesia 2045. The Alpha Generation that grows up in technological developments and global challenges requires high emotional intelligence to be able to adapt well in the future. using a qualitative method with a literature study approach, which collects theories and information from academically accountable sources such as books, journals, the Bible, and online media. The researcher selected relevant literature materials to discuss the role of Christian Religious Education teachers in shaping the emotional quotient (EQ) of Alpha Generation children. The main purpose of this study is to explore how PAK teachers can play a role in shaping children's EQ through a learning approach based on Christian religious values, as well as to find out the strategies and methods used in teaching to improve children's emotional intelligence. The results of this study are expected to contribute to the development of character education, especially in the context of Christian religious education, to support the achievement of the Golden Indonesia 2045 by producing a generation that is emotionally, socially, and spiritually intelligent.